On a Class of Variational-Hemivariational Inequalities Involving Upper Semicontinuous Set-Valued Mappings - Guo-ji Tang; Zhong-bao Wang; Hong-ling Zhang (Abstract and Applied Analysis)
This paper is devoted to the various coercivity conditions in order to guarantee existence of solutions and boundedness of the solution set for the variational-hemivariational inequalities involving upper semicontinuous operators. The results presented in this paper generalize and improve some known results.